Revisiting Balance of Threat Theory: The Case of Contemporary Southeast Asia in the Context of Great Power Contestation - Widian, Rizky (Parahyangan Center for International Studies, 2025)
Southeast Asian countries, situated at the heart of the Indo-Pacific, are increasingly exposed to intensifying great power competition between China and the United States (US). According to Balance of Threat (BoT) theory, states are more likely to align tightly with a less threatening power in response to rising threats characterized by a rival's aggregate power, geographical proximity, offensive capabilities, and aggressive intentions. Based on these indicators, BoT would predict stronger alignment between Southeast Asian countries and the US to balance against the perceived threat from China. However, alignment behavior in the region varies, suggesting the need for closer empirical scrutiny. This study reexamines BoT theory in the Southeast Asian context through a structured comparative empirical analysis of ten countries between 2000 and 2021. The findings reveal that while BoT’s core prediction holds in some cases, alignment outcomes are mixed. Thus, the theory receives only partial support in explaining Southeast Asian states’ responses to China’s rise. Keywords: Balance of Threat theory, Southeast Asia, alignment behavior, great power competition, US-China rivalry, Indo-Pacific, threat perception, security cooperation, comparative analysis, regional security